European Trade and Colonial Conquest (vol. 1): By Biplab Dasgupta (London: Anthem Press, 2005. 398 pages.) (American Journal of Islam and Society, 2006)
European Trade and Colonial Conquest is authored by Biplab Dasgupta, arenowned political and social activist from Calcutta who taught economics atCalcutta University and was a member of the Parliament of India for severalyears. He has authored many books on various aspects of India’s socioeconomicand political life in the post-independence era, such as the oil industry,the Naxalite movements, trends in Indian politics, labor issues and globalization,agrarian change and technology, rural change, urbanization, and migration.The present book primarily focuses on the evolution of Bengal’s economyand society over the precolonial period, beginning from prehistoric days.Even though there are writings on Bengal’s colonial history, we know verylittle about its precolonial past except for the names of kings, the chronologyof dynasties, and scattered references to urban settlements.Dasgupta shows a specific interest in highlighting the socioeconomichistory of the last two and half centuries, from Vasco de Gama’s journey toIndia in 1498 to the battle of Palashi in 1757. The author asserts that heexplores in detail the socioeconomic and political context of Bengal thatfacilitated the transfer of power to European hands, because historians generallyignore this rather quite long and critical period. He, therefore, commentsthat this is “less a book on pre-colonial Bengal” and more a book onEuropean trade and colonial conquest (p. vii). The book explains howEuropean commercial enterprise in Bengal gathered political power throughits control over trade and gradually transformed itself into a colonial power.Although the Mughals held political power during this period, the economicpower and control of the Indian Ocean trade routes were gradually slippinginto European hands.It is believed that Clive’s victory at the battle of Palashi led to the colonialconquest of Bengal. However, focusing on Bengal’s socioeconomic ...